Gut microbiome profile in psoriatic patients treated and untreated with biologic therapy. Issue 6 (28th January 2021) - Valentini, Virginia; Silvestri, Valentina; Marraffa, Federica; Greco, Giulia; Bucalo, Agostino; Grassi, Sara; Gagliardi, Antonella; Mazzotta, Annamaria; Ottini, Laura; Richetta, Antonio Giovanni
Abstract: There are increasing data about the role of the gut microbiome in various autoimmune diseases, including psoriasis, a chronic inflammatory and immune‐mediated disease. Current treatment strategies in psoriasis include immunomodulating biologic agents. A variable response to this type of therapy has been reported in psoriatic patients. A possible effect of biologic therapy on the gut microbiome composition has been suggested, but data are still limited. The aim of this study was to compare the gut microbiome composition between psoriatic patients treated and untreated with biologic drugs in order to identify differences which may highlight the potential impact of the treatment on the gut microbiome. 16S rRNA sequencing and bioinformatic analyses were performed on the fecal samples of 30 psoriatic patients with similar clinicopathological features, 10 of whom were undergoing biologic therapy and 20 not receiving systemic therapy. Alpha and beta diversity significantly differed between the two groups of patients. A reduced bacterial biodiversity in the group of treated patients compared with the group of untreated patients was observed. Differential relative abundances of key gut microbial communities, including Akkermansia muciniphila and Bacteroides plebeius, were identified between the two groups of patients. This study showed that biologic therapy may have an impact on the composition of the gut microbiome of psoriatic patients. Gut microbiome composition could be used as an indicator of response to therapy and the modulation of the microbial composition could help to restore the intestinal symbiosis in psoriatic patients.